Production of virgin coconut oil (VCO) via combination of microwave and centrifugation method - Wong, Pei Wen (2010)
In this study, the potential of the centrifugation method and the combination of microwave and centrifugation method in demulsification (emulsion breaking) of coconut milk emulsion is investigated. The conventional methods in producing Virgin Coconut Oil (VCO) by using drying, fermentation and cold pressing need longer time to break these emulsions. For the research purpose, the coconut milk without added water from local market was used as samples. For the centrifugation method, the centrifuge speeds were varied from 6000 to 12000rpm and centrifugation times were varied from 30 to 105min. For the combination of microwave and centrifugation method, the microwave powers of 360, 540 and 720Watts were used and centrifugation times were varied from 60 to 105min. From the results obtained, for centrifugation method, the highest yield of 37.3% VCO is obtained at 12000rpm and 105min; while, for the combination of microwave and centrifugation method, the highest yield of 46.88% VCO is obtained at 720W of microwave power at 12000rpm and 105min. Results showed that the combination of microwave and centrifugation method gives a better yield of VCO. Due to its fast and higher yield of VCO, combination of microwave and centrifugation method can be used as an alternative demulsification method for oil-in-water coconut milk emulsions.